Synergistic effects of Candida albicans and Porphyromonas gingivalis biofilms on epithelial barrier function in a 3D aspiration pneumonia model - Wronowska, Ewelina; Guevara-Lora, Ibeth; Brankiewicz, Aleksandra; Bras, Grazyna; Zawrotniak, Marcin; Satala, Dorota; Karkowska-Kuleta, Justyna; Budziaszek, Joanna; Koziel, Joanna; Rapala-Kozik, Maria (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPolymicrobial infections involving Candida albicans and Porphyromonas gingivalis represent a significant challenge in maintaining epithelial barrier integrity. This study explores their synergistic effects on epithelial cells using an air-liquid interface (ALI) model.MethodsMixed-species biofilms were developed and analyzed for their impact on epithelial permeability and tight junction proteins. The effects of biofilm supernatants on IL-8 secretion and oxidative stress markers were also evaluated. The role of P. gingivalis proteases was assessed using a gingipain-null mutant (ΔKΔRAB) compared to the wild-type strain (W83). Survival experiments were conducted using Galleria mellonella larvae to examine the pathogenicity of dual-species biofilms.ResultsMixed-species biofilms significantly increased epithelial permeability and disrupted tight junction proteins, as evidenced by reduced levels of ZO-1 and E-cadherin. These changes were accompanied by oxidative stress, characterized by decreased HO-1 expression and enhanced Bax/Bcl-xL ratios, indicating increased pro-apoptotic activity. Supernatants from dual-species biofilms demonstrated a pronounced effect on epithelial cells, modulating IL-8 secretion and exacerbating oxidative damage. C. albicans was identified as the dominant driver of pro-inflammatory responses, while P. gingivalis contributed through immune modulation and enzymatic activity, primarily via gingipains. The ΔKΔRAB mutant biofilms caused less epithelial disruption and oxidative stress compared to the wild-type, highlighting the critical role of gingipains in pathogenesis.DiscussionSurvival experiments using Galleria mellonella larvae supported these findings, highlighting the reduced survival associated with dual-species biofilms and the potential for high-dose antimicrobial therapies to mitigate this effect. These results emphasize the cooperative mechanisms of C. albicans and P. gingivalis in compromising epithelial barriers and underline the importance of combination therapies targeting both fungal and bacterial components in polymicrobial infections.